2005
DOI: 10.1001/archinte.165.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption and Stroke Risk in Elderly Individuals

Abstract: Among elderly individuals, consumption of tuna or other broiled or baked fish is associated with lower risk of ischemic stroke, while intake of fried fish or fish sandwiches is associated with higher risk. These results suggest that fish consumption may influence stroke risk late in life; potential mechanisms and alternate explanations warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(93 citation statements)
references
References 29 publications
2
87
1
3
Order By: Relevance
“…Given the known health benefits of fish consumption [1,2,20,26] it is of great importance that efforts such as this are made in order to accurately measure fish intake in dietary trials. Future research should aim to expand on these findings, to the development of a comprehensive canned fish and seafood database which can be used in a wide variety of future trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the known health benefits of fish consumption [1,2,20,26] it is of great importance that efforts such as this are made in order to accurately measure fish intake in dietary trials. Future research should aim to expand on these findings, to the development of a comprehensive canned fish and seafood database which can be used in a wide variety of future trials.…”
Section: Resultsmentioning
confidence: 99%
“…Habitual fish consumption has been associated with a range of health benefits, including decreased incidence of stroke and heart failure and decreased mortality from cardiovascular disease [1][2][3][4][5]. There is evidence that canned fish and seafood products such as canned tuna are increasing in popularity as a convenient source of fish in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Population studies demonstrated that the high intake of LC-PUFA n-3 deriving from fish oils as well as see fish was associated with a reduced occurrence of ischemic heart disease, myocardial infarction and stroke, but potentially it can be associated with a reduced occurrence of AD due to vessels mechanisms [25][26][27]. An impact of fish and meat intake frequency on dementia risk was assessed in the study PAQUID (Personnes Agées QUID) in the group of 1416 elderly people from France (>68 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that fish consumption has beneficial effects on stroke mortality in men and women [191,192], especially on ischemic stroke but not against hemorrhagic stroke. This is further supported by the results of a metaanalysis, which also showed that increased fish consumption reduced the incidence of total stroke and ischemic stroke, and decreased stroke-related mortality [193].…”
Section: -3 Fatty Acids and Strokementioning
confidence: 99%